Business Writing Style Guide - Morris, John; Zwart, Julie (Open textbook library., 2020)
It is the goal of this book to help students do the following:• Apply basic concepts for effective and concise business writing.• Compile a well written report acceptable within a business context.• Follow a writing process designed for business students.• Demonstrate critical thinking, reasoning, and persuasion.• Communicate in writing using a business model.• Apply resources for improving business writing skills.